INTERNAL UNIVERSITY GOVERNANCE AND SOCIAL RELEVANCE. ANALYSISOF PUBLIC HIGHER EDUCATION - Bazán Rezkalah, Sylvia E. (2023)
In the current context, despite the pandemic, different activities continue to be carried out in the public sphere, regardless of not knowing exactly when it would end and what its consequences would be. In particular, in the higher education sector, in which the institutional management of the publicuniversity is not adequate, the inefficiency of internal governance and social relevance do not comply with social responsibility, having a negative impact on both the students as well as in society. The objective was to analyze the elements of internal university governance and the social relevance of a national universityin Lima, Peru in 2020. The methodology was the qualitative method, of an exploratory and interpretive nature and hermeneutical design. The techniques used were open, semistructured interviews, analysis of specializedbibliography and validation of the questions by expert judgment. The results established that Peruvian public universities have an improperorganizational system. Those who holdpower do not take into account the values and principles, circumstances that prevent university social relevance and, therefore, irresponsibility towards society is established; except, very few exceptions. The conclusion determined that it is necessary, as a priority, to manage personal and institutional change at the management level and to carry out feasibility studies developed for our context, with the purpose of building a convenient paradigm for higher education in our country where responsibility social university (RUS), covers the population as the primary objective of university work with the aim of generating public value in society